Contextual Approach in Arabic Language Learning: Developing Students' Critical Thinking Skills/ النهج السياقي في تعلم اللغة العربية: بناء مهارات التفكير النقدي لدى الطلاب - Siti Wulan Asih; Naila Rohmaniyah (IJAS: International Journal of Arabic Studies, 2024)
This study aims to examine the effectiveness of a contextual approach in Arabic language learning to develop students' critical thinking skills. The contextual approach involves linking lesson materials with students' everyday life situations, helping them understand Arabic in relevant contexts. This research employs a qualitative method with a descriptive approach. The subjects of the study are madrasah students learning Arabic. Data were collected through observation, interviews, and questionnaires measuring students' critical thinking skills and learning motivation. Data analysis was conducted using thematic techniques to understand the impact of this approach on the learning process. The results of the study indicate that the application of the contextual approach significantly improves students' critical thinking skills. Students were more able to analyze Arabic texts and apply them in real-life situations. Additionally, this approach also enhanced students' motivation to learn Arabic as they felt more connected to the lesson materials. The study concludes that the contextual approach is effective in developing critical thinking skills and increasing students' learning motivation in Arabic language education